Correction: Inhibitory effect of a genistein derivative on pigmentation of Guinea pig skin. Issue 13 (13th February 2018) - Zhou, Quancheng; Feng, Chuanxing; Ruan, Zheng
Abstract : Correction for 'Inhibitory effect of a genistein derivative on pigmentation of Guinea pig skin' by Quancheng Zhou et al., RSC Adv., 2017, 7, 7914–7919.